Issues and challenges in enhancing the quality of private transnational higher education in Malaysia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
The rapid growth in the demand for higher education in Malaysia and the lack of capacity of the national system to meet this demand have given rise to the emergence and expansion of private transnational higher education providers in the country.